The clinical utility of structural neuroimaging with MRI for diagnosis and differential diagnosis of dementia: a memory clinic study - Hentschel, Frank; Kreis, Markus; Damian, Marinella; Krumm, Bertram; Frölich, Lutz (International journal of geriatric psychiatry, 2005)
Objectives The individual contribution to the final comprehensive clinical diagnosis of neuropsychology (NP) and magnetic resonance imaging (MRI), respectively, was quantified in a specialized tertiary care setting to investigate the added clinical value of routine MRI. Methods In 106 patients referred to a university memory clinic for the work-up of cognitive disturbances the primary care diagnosis, the initial clinical neuropsychiatric diagnosis, the neuropsychological and MRI diagnoses, and the final comprehensive clinical diagnosis were documented. The neuropsychological investigation was performed using the CERAD test battery. MRI was performed using T1, double echo and FLAIR sequences without contrast medium. The change of the final comprehensive clinical diagnosis in relation to the initial neuropsychiatric diagnosis was used to determine the diagnostic contribution of both, MRI and NP. Results NP and MRI led to a significant change of the final comprehensive diagnosis in 26% of patients (CI: 0.26 ± 0.09; p < 0.05). In addition, three cases of secondary dementias, and six cases of vascular encephalopathy without dementia were recognized by MRI. Sensitivity, specificity, and the positive predictive value were higher for NP and MRI, respectively, than for the initial clinical diagnosis alone. Conclusion MRI as well as neuropsychological testing improves early detection and differential diagnosis of dementia and additionally supplies clinically relevant findings. MRI carries added clinical value in the investigation of dementias. Copyright © 2005 John Wiley & Sons, Ltd.